2014
DOI: 10.1103/physrevb.90.115406
|View full text |Cite
|
Sign up to set email alerts
|

Resistance-voltage dependence of nanojunctions during electromigration in ultrahigh vacuum

Abstract: The electrical resistance R of metallic nanocontacts subjected to controlled cyclic electromigration in ultra-high vacuum has been investigated in-situ as a function of applied voltage V . For sufficiently small contacts, i.e., large resistance, a decrease of R(V ) while increasing V is observed.This effect is tentatively attributed to the presence of contacts separated by thin vacuum barriers in parallel to ohmic nanocontacts. Simple model calculations indicate that both thermal activation or tunneling can le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
9
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
6
9
1
Order By: Relevance
“…This negative slope was attributed to a nanocontact of a large area in the tunneling regime and a change of the distance of the two electrodes of the nanocontact due to either thermal expansion, when the contact is heated resistively, or electrostatic forces due to the applied voltage. Although tunneling is unlikely here due to the large distance of the electrodes, the structure of the sample is in good agreement with the structure proposed in [36]: There is a large area of the slit, because its width is 200 µm and within the slit, it is easily possible to have many tunneling contacts in parallel at an earlier stage of the electromigration process. Also the assumption of a grainy structure of the sample taken in Ref.…”
Section: Overall Comparison With Previous Resultssupporting
confidence: 86%
“…This negative slope was attributed to a nanocontact of a large area in the tunneling regime and a change of the distance of the two electrodes of the nanocontact due to either thermal expansion, when the contact is heated resistively, or electrostatic forces due to the applied voltage. Although tunneling is unlikely here due to the large distance of the electrodes, the structure of the sample is in good agreement with the structure proposed in [36]: There is a large area of the slit, because its width is 200 µm and within the slit, it is easily possible to have many tunneling contacts in parallel at an earlier stage of the electromigration process. Also the assumption of a grainy structure of the sample taken in Ref.…”
Section: Overall Comparison With Previous Resultssupporting
confidence: 86%
“…The results of the electromigration thinning procedure showed that contacts in the tunneling regime were formed and are discussed in detail in Ref. 19. In this publication, the results of the electromigration thinning procedure are found to be similar to results obtained by electromigration of nanobridges fabricated using standard electron beam lithography methods and on-chip microstructured Si 3þx N 4Àx membrane masks.…”
Section: Resultssupporting
confidence: 68%
“…Indeed, even a hydrogen molecule, present in the area of the metallic (Pt) contact, could be viewed as a molecular electronics device (Smit et al, 2002;Csonka et al, 2003;and Jel ınek et al, 2006). For Au contacts investigated by the electromigration method, mainly oxygen had a clear effect, leading to uncontrolled behavior and early breaking of the forming nanocontact at room temperature (St€ offler et al, 2014). On the other hand, at liquid-helium temperatures the formation of atomic chains in Au and Ag was enhanced in the presence of oxygen (Thijssen et al, 2006).…”
Section: Few Atom Contactsmentioning
confidence: 99%